Falls in peripheral eosinophil counts parallel the late asthmatic response. - Cookson,WO; Craddock,CF; Benson,MK; Durham,SR (Am Rev Respir Dis, 1989)
Peripheral eosinophil counts were measured at intervals before and after control and allergen inhalation in 14 asthmatic subjects. A relative fall in eosinophil counts was noted 9 h after allergen challenge, in contrast to the diurnal increase seen on the control day (p = 0.005). This fall in eosinophil count correlated strongly with the magnitude of the late asthmatic response (r = -0.72, p = 0.003) and with the changes in bronchial responsiveness to histamine at 3 and 24 h after allergen was given (r = 0.54, p = 0.044 and r = 0.82, p less than 0.001, respectively). The findings demonstrate eosinophil kinetics are related to the occurrence of late-phase reactions and to the associated worsening of bronchial hyperreactivity.